ความสำคัญของความผิดปกติของยีนพี 16 ที่เกิดจากเมททิเลชั่นในการเป็นปัจจัยพยากรณ์โรคและปัจจัยทำนายการตอบสนองต่อการรักษาในผู้ป่วยมะเร็งโพรงหลังจมูก - สมชัย ลิมปการณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Objective To determine the significance of p I6 methylation as prognostic factor of survival and recurrence and predictive factor of response in nasopharyngeal carcinoma patients. Method Between 1994 and 1999, 55 patients were selected from nasopharyngeal carcinoma patients who were diagnosed by tissue biopsy with complete clinical data. The patients were classified into two groups, with and without p l6 methylation, detected by MS-PCR from tumor s DNA extract. Survival times, recurrence rates and response rates were analyzed for difference determination between groups. Univariate and multivariate analysis were also performed to determine dependent and independent prognostic factors in NPC. Results Overall survival times, response rates and recurrence rates in both groups were not significant differrent. The median overall survival time were 31.35 and 28.40 months in the patients without and with p I6 methylation, respectively (p=0.054). The response rates were 100% and 82.8% in the patients without and with p I6 methylation, respectively (p=0.053). The recurrence rates, 16% and 23.8% in each group, that were not different (p=0.071). But median progression-free survival times in both groups were significant different, that were 29.00 and 23.20 months in the patients without and with p I6 methylation, respectively (p=0.03). From univariate and multivariate analysis, p I6 methylation and duration of symptoms were found as independent prognostic factors in NPC. Conclusion PI6 methylation was found as independent prognostic factor in NPC. The median progressionfree survival times in both groups were significant different, which in the patients without p I6 methylation was longer than in the patients with p I6 methylation. PI6 methylation was not found as prognostic factors of recurrence and predictor of response.